Bibliography of the International Arthurian Society. - Busch, Nathanael (Bibliography of the International Arthurian Society ;, 2016)
The purpose of the BIAS is, year by year, to draw attention to all scholarly books and articles directly concerned with the matière de Bretagne. The bibliography aims to include all books, reviews and articles published in the year preceding its appearance, an exception being made for earlier studies which have been omitted inadvertently. The present volume contains over 700 entries on relevant publications that were published in 2014.